As vogais médias pretônicas na fala de Vitória - Leite, Melina de Figueiredo (2014)
In capixaba variety, as well as in Brazilian Portuguese (BP), prestressed vowels can be produced in three ways: mid-high, mid-low and high. We analyze the influence of linguistic and social variables on the variation of the mid prestressed vowel, in a corpus composed of 20 of the 46 interviews that constitute PortVix sample (Portuguese spoken in the city of Vitoria). In PortVix, speakers were stratified by gender / sex, age and educational level. In addition to social factors, we also observed the performance of linguistic variables , such as nasality, the kind of tonic , the distance between the tonic and mid prestressed vowel, the syllabic structure, the point and manner of articulation of consonants preceding and following the vowel after mid prestressed vowel and atonicity. We verified with this study that there are high rates of mid-low vowels, which was not considered by Nascentes (1953), which proposes a dialectal division of Brazil based on the realization of mid prestressed. Based on the observation mentioned, consider that Vitoria is possibly in the transition zone between the northern and southern dialects proposed by Nascentes. We also verified that the most relevant factor for both the raising and the lowering of the mid prestressed was the kind of tonic. Also, we did a short acoustic analysis of mid prestressed in Vitoria speech. Finally, we observe from the sociolinguistic and acoustic analysis, harmonization is more conclusive for lowering than for raising.